2006
DOI: 10.1084/jem.20051938
|View full text |Cite
|
Sign up to set email alerts
|

The polymerase complex genes contribute to the high virulence of the human H5N1 influenza virus isolate A/Vietnam/1203/04

Abstract: H5N1 influenza viruses transmitted from poultry to humans in Asia cause high mortality and pose a pandemic threat. Viral genes important for cell tropism and replication efficiency must be identified to elucidate and target virulence factors. We applied reverse genetics to generate H5N1 reassortants combining genes of lethal A/Vietnam/1203/04 (VN1203), a fatal human case isolate, and nonlethal A/chicken/Vietnam/C58/04 (CH58) and tested their pathogenicity in ferrets and mice. The viruses' hemagglutinins have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
309
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 336 publications
(333 citation statements)
references
References 41 publications
21
309
2
1
Order By: Relevance
“…Over the last decade, reconstitution of recombinant vRNP complexes in transfected cells from co-expressed PB1, PB2 and PA polymerase subunits, NP and vRNA, followed by the analysis of reporter gene expression/activity or a direct analysis of accumulating viral RNAs by a primer extension assay, has become the method of choice for studying influenza virus polymerase activity in vivo (Deng et al, 2006;Fodor et al, 2002;Gabriel et al, 2005;Labadie et al, 2007;Mullin et al, 2004;Pleschka et al, 1996;Salomon et al, 2006;Vreede et al, 2004). However, as the RNP reconstitution assay involves only the minimal components required for viral transcription and replication, it might not reflect all of the regulatory events that occur during transcription and replication in virus-infected cells.…”
Section: Regulation Of Viral Rna Accumulation During Infection and Inmentioning
confidence: 99%
“…Over the last decade, reconstitution of recombinant vRNP complexes in transfected cells from co-expressed PB1, PB2 and PA polymerase subunits, NP and vRNA, followed by the analysis of reporter gene expression/activity or a direct analysis of accumulating viral RNAs by a primer extension assay, has become the method of choice for studying influenza virus polymerase activity in vivo (Deng et al, 2006;Fodor et al, 2002;Gabriel et al, 2005;Labadie et al, 2007;Mullin et al, 2004;Pleschka et al, 1996;Salomon et al, 2006;Vreede et al, 2004). However, as the RNP reconstitution assay involves only the minimal components required for viral transcription and replication, it might not reflect all of the regulatory events that occur during transcription and replication in virus-infected cells.…”
Section: Regulation Of Viral Rna Accumulation During Infection and Inmentioning
confidence: 99%
“…The haemagglutinins of the two viral strains were found to have six amino acid differences, identical cleavage sites, and avian-like alpha-(2,3)-linked receptor specificity (68). Surprisingly, it was found that exchanging haemagglutinin and neuraminidase genes did not alter pathogenicity, but substituting CH58 polymerase genes completely attenuated VN1203 virulence and reduced viral polymerase activity (68).…”
Section: Evolution Of Virulence Properties In Influenza Virusesmentioning
confidence: 99%
“…Yet another type of high-virulence character that has been found in some of those dangerous H5N1 strains that now circulate in birds is located in viral RNA polymerase complex genes (67,68). It was shown in one study that a single amino acid substitution, from glutamic acid to lysine at position 627 of the PB2 protein (which is one of the components of the viral RNA polymerase), was enough to convert a non-lethal H5N1 influenza A virus isolated from a human to a lethal virus in mice (67).…”
Section: Evolution Of Virulence Properties In Influenza Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…101 The polymerase complex genes 102 contribute to the high virulence of the human H5N1 infl uenza virus isolate A/Vietnam/1203/04. This observation underscores the importance of novel antivirals targeting the polymerase for further development for the therapy and prophylaxis of human and avian infl uenza virus infections.…”
Section: Influenza Virus Rna Polymerase Inhibitorsmentioning
confidence: 99%